PROBLEMS OF ORGANIZING THE ACTIVITIES OF MANAGEMENT BOARDS IN HIGHER EDUCATION INSTITUTIONS ON THE EXAMPLE OF THE EXPERIENCE OF FOREIGN COUNTRIES - Yakubov Azizjon Tajiboevich (PEDAGOGS, 2024)
Abstract: Governing boards play a critical role in the governance and decision-making processes of higher education institutions worldwide. However, the organization of these councils presents unique challenges that require careful consideration and strategic planning. Based on the experience of foreign countries, this article examines the problems encountered in the organization of management councils in higher education institutions and provides valuable lessons for improvement.